Dark energy survey year 1 results: Constraining baryonic physics in the Universe. Issue 4 (15th February 2021) - Huang, Hung-Jin; Eifler, Tim; Mandelbaum, Rachel; Bernstein, Gary M; Chen, Anqi; Choi, Ami; García-Bellido, Juan; Huterer, Dragan; Krause, Elisabeth; Rozo, Eduardo; Singh, Sukhdeep; Bridle, Sarah; et al.
ABSTRACT: Measurements of large-scale structure are interpreted using theoretical predictions for the matter distribution, including potential impacts of baryonic physics. We constrain the feedback strength of baryons jointly with cosmology using weak lensing and galaxy clustering observables (3 × 2pt) of Dark Energy Survey (DES) Year 1 data in combination with external information from baryon acoustic oscillations (BAO) and Planck cosmic microwave background polarization. Our baryon modelling is informed by a set of hydrodynamical simulations that span a variety of baryon scenarios; we span this space via a Principal Component (PC) analysis of the summary statistics extracted from these simulations. We show that at the level of DES Y1 constraining power, one PC is sufficient to describe the variation of baryonic effects in the observables, and the first PC amplitude ( Q 1 ) generally reflects the strength of baryon feedback. With the upper limit of Q 1 prior being bound by the Illustris feedback scenarios, we reach 20 per cent improvement in the constraint of S_8=σ _8(Ω _m/0.3)^0.5=0.788^+0.018_-0.021 compared to the original DES 3 × 2pt analysis. This gain is driven by the inclusion of small-scale cosmic shear information down to 2.5 arcmin, which was excluded in previous DES analyses that did not model baryonic physics. We obtain S_8=0.781^+0.014_-0.015 for the combined DES Y1+Planck EE+BAO analysis with a non-informative Q 1 prior. In terms of the baryon constraints, we measure Q_1=1.14^+2.20_-2.80 for DES Y1 only and Q_1=1.42^+1.63_-1.48 for DESY1+Planck EE+BAO, allowing us to exclude one of the most extreme AGN feedback hydrodynamical scenario at more than 2σ.